Content selection and curation for web archiving: The gatekeepers vs. the masses - Milligan, Ian; Ruest, Nick; Lin, Jimmy (JCDL '16 : proceedings of the 16th ACM/IEEE-CS Joint Conference on Digital Libraries : June 19-23, 2016, Newark, NJ, USA, 2016)
Any preservation effort must begin with an assessment of what content to preserve, and web archiving is no different. There have historically been two answers to the question "what should we archive?" The Internet Archive's broad entire-web crawls have been supplemented by narrower domain-or topic-specific collections gathered by numerous libraries. We can characterize this as content selection and curation by "gatekeepers". In contrast, we have witnessed the emergence of another approach driven by "the masses" - we can archive pages that are contained in social media streams such as Twitter. The interesting question, of course, is how these approaches differ. We provide an answer to this question in the context of a case study about the 2015 Canadian federal elections. Based on our analysis, we recommend a hybrid approach that combines an effort driven by social media and more traditional curatorial methods.